Report on quality estimation for selection purposes in 300 apomictic interspecific hybrids of the population Br19 - Hernández, Luis Miguel; Mazabel, Johanna; Castiblanco, Valheria (Bioversity International and the International Center for Tropical Agriculture, 2021)
The aim of this work was to estimate the nutritional value of 300 hybrids from Urochloa interspecific breeding program. Plant biomass was harvested and subjected to a bromatological analysis to evaluate crude protein, neutral and acid detergent fiber, and in vitro digestibility using standardized methods. A large proportion of the hybrids showed better nutritional values than the genotypes used as controls. We expect to build a selection index with nutritional quality values and other previously evaluated traits to identify the best hybrids for selection.